The Role of TikTok Shop Influencers through "Toxic" Content in Triggering Impulse Buying among Generation Z for Fast Fashion Product - Marlisye Aprilia Sarah Togas; Bambang Raditya Purnomo (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2026)
The rapid growth of TikTok Shop as a social commerce platform has led to the emergence of 'toxic content' produced by influencers as a marketing tactic that effectively influences Generation Z's shopping behavior. This study investigates the role of TikTok Shop influencers and their 'toxic content' in stimulating impulse buying behavior among Generation Z consumers in the fast fashion sector, focusing on the psychological mechanisms involved, the most frequently purchased product categories, and the broader impacts of these consumption patterns. A qualitative research approach with a phenomenological design was used, and data were gathered through in-depth interviews with eight informants: six Generation Z consumers aged 19–24 years and two active TikTok Shop fashion influencers, selected via purposive sampling. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña (2014). Findings show that 'toxic content' acts as a stimulus within the Stimulus-Organism-Response (S-O-R) theoretical framework, triggering impulse buying within minutes by evoking positive emotions and urgency. The Fear of Missing Out (FOMO) mechanism, driven by emotional triggers like time scarcity, social proof, and exclusivity, was the most dominant psychological factor. The most commonly purchased items were tops, coordinated sets, aesthetic bottoms, locally-made footwear, and accessories. The effects of 'toxic content' are financial, psychological, social, and environmental. This study advances influencer marketing literature and provides insights into Generation Z’s consumer behavior in the social commerce age.